Employing x-ray photoelectron spectroscopy for determining layer homogeneity in mixed polar self-assembled monolayers - Hehn, Iris; Schuster, Swen; Wächter, Tobias; Abu-Husein, Tarek; Terfort, Andreas; Zharnikov, Michael; Zojer, Egbert (The journal of physical chemistry letters, 2016)
Self-assembled monolayers (SAMs) containing embedded dipolar groups offer the particular advantage of changing the electronic properties of a surface without affecting the SAM-ambient interface. Here we show that such systems can also be used for continuously tuning metal work functions by growing mixed monolayers consisting of molecules with different orientations of the embedded dipolar groups. To avoid injection hot-spots when using the SAM-modified electrodes in devices, a homogeneous mixing of the two components is crucial. We show that a combination of high-resolution X-ray photoelectron spectroscopy with state-of-the-art simulations is an ideal tool for probing the electrostatic homogeneity of the layers and thus for determining phase separation processes in polar adsorbate assemblies down to inhomogeneities at the molecular level.